United Republic of Tanzania : Request for a Three-Year Policy Support Instrument. (IMF Staff Country Reports; Country Report ;, 2014)
KEY ISSUES Economic background and outlook. Tanzania has enjoyed strong and stable growth, projected to remain at 7 percent next year and in the medium term. Inflation is at 6 percent, gradually converging to the authorities' 5 percent medium-term objective. The external current account deficit remains among the largest in the region, at 14 percent of GDP this year. Fiscal revenue shortfalls and overruns in domestically-financed spending led the deficit to rise to 6.8 percent of GDP in 2012/13. Revenue shortfalls in 2013/14 compared to the budget approved by parliament have prompted the authorities to undertake expenditure cuts during the fiscal year in an effort to meet their 5 percent of GDP target. Based on the debt sustainability analysis, Tanzania remains at low risk of debt distress. Recent program engagement. Tanzania concluded its final review under a Standby Credit Facility (SCF) arrangement, together with its Article IV consultations, on April 25, 2014. The SCF expired on April 30, 2014. Key challenges. Over the next three years, policymakers will face several challenges, including the following: -- Step up needed investment in infrastructure while protecting critical social spending. These objectives will need to be pursued following careful prioritization, to preserve government debt sustainability. -- Prepare for natural gas. If recent discoveries of sizeable offshore natural gas deposits are confirmed as commercially viable, sizable fiscal revenues would need to be managed to bring benefits to all Tanzanians. Against this background, the authorities are requesting a three-year PSI to be in place by the start of FY2014/15. They see the PSI as an appropriate instrument to underpin the close policy dialogue with staff, provide a positive signal to donors and markets, and safeguard policy discipline. Staff supports the authorities' request for a PSI.